2022
DOI: 10.3390/brainsci12070860
|View full text |Cite
|
Sign up to set email alerts
|

Delta Opioid Receptors and Enkephalinergic Signaling within Locus Coeruleus Promote Stress Resilience

Abstract: The noradrenergic nucleus locus coeruleus is a key component of the stress circuitry of the brain. During stress, the neuropeptide corticotropin-releasing factor (CRF) is secreted onto LC, increasing LC output and norepinephrine concentration in the brain, which is thought to promote anxiety-like behavior. LC is also innervated by several structures that synthesize and release the endogenous opioid peptide enkephalin onto LC upon stressor termination. While the role of CRF neurotransmission within LC in mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Previous studies have shown lesions or blockade of LC activity reverses neuropathic injury-induced hypersensitivity( 8, 9 ). Therefore, it stands to reason that other endogenous inhibitory systems within the LC may produce similar behavioral responses( 25, 5963, 82, 86, 9097 ). Future work should pursue this hypothesis to identify new, potentially analgesic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown lesions or blockade of LC activity reverses neuropathic injury-induced hypersensitivity( 8, 9 ). Therefore, it stands to reason that other endogenous inhibitory systems within the LC may produce similar behavioral responses( 25, 5963, 82, 86, 9097 ). Future work should pursue this hypothesis to identify new, potentially analgesic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…These studies establish that TCAP-1 inhibits both CRF stress and addiction-related behaviors, but these attenuating effects on behavior associated with cocaine -a psychostimulant -may not necessarily generalize to other classes of psychoactive drugs, such as opioids. However, because the opioid-associated neurological circuit encompasses both stress-and addiction-related behaviors (Crowley and Kash 2015; Haun et al 2022;Leconte et al 2022;Rysztak and Jutkiewicz 2022;Simmons et al 2020;Tkaczynski et al 2022;Zhang et al 2022), and because opioid cessation results in withdrawal which is itself as stressor, it is possible that TCAP-1 could have utility in facilitating opioid abstinence.…”
Section: Introductionmentioning
confidence: 99%